VD_FINDINFO HC / 2014 / 456 vom 13. Juni 2014 - VD Tribunal cantonal (2014)
MESURE PROVISIONNELLE, SERVITUDE, POSSESSION, CONTRAT DE FOURNITURE D'ÉNERGIE | 737 CC, 929 al. 2 CC, 261 CPC (CH), 308 al. 1 let. b CPC (CH), 308 al. 2 CPC (CH), 317 al. 2 CPC (CH)